(untitled) (Research, Society and Development, 2020)
The suspension of in classroom teaching activities is one of the many changes in the lives of thousands of faculty and college students due to the COVID-19 pandemic. This study deals with a pedagogical adaptation for remote teaching of topics in epidemiology in a public higher education institution. This is a descriptive study related to three courses offered regularly by Nursing and Pharmacy programs that had didactic planning suitable for remote teaching via the “Special Home Exercise Scheme”. Teaching plans and methodologies were adapted to use digital technologies and a virtual learning environment. The current epidemiological scenario was used as a basis for preparing questions and situation analysis in the adapted remote format. With regards to the general structure of the curses and teaching effectiveness during the pandemic, it was found that the adoption of active teaching methodologies centering on the epidemiology of COVID-19 itself, and the appreciation of the students’ prior knowledge on this topic are central to promote active learning and the development of important skills for future health professionals. All relevant topics in epidemiology were suitable for adaptation for remote learning, and the connection maintained between teachers and students proved to be an important ally in facing the pandemic. It is important to take into consideration limitations of remote education, such as lack of broad access to the internet and of digital technologies, and that topic needs to continue to be widely discussed by institutions of higher education.